Peran Lembaga Pemasyarakatan Dalam Upaya Pembinaan Terhadap Pelaku Residivis Tindak Pidana Narkotika : (Studi Kasus Lembaga Pemasyarkatan Kelas IIA Gorontalo) - Rian Tuta; Dian Ekawaty Ismail; Mohamad Rivaldi Moha (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
The purpose of this activity is to determine the success of the role of efforts to develop the Gorontalo Class IIA Penitentiary for prisoners, one of which is prisoners who have a high level of awareness so that there will be no repetition of narcotics crimes (narcotics recidivism). The research method used is a type of empirical legal research, namely the Sulatul Meltholm research method, which has the ultimate function of seeing law in a real sense and studying how law works in the social environment. The results of the research obtained on the role of Correctional Institutions in efforts to guide recidivist perpetrators of narcotics crimes in Gorontalo Class IIA Prisons have not been effective. The factors that hinder efforts to provide guidance to recidivist narcotics criminals are the lack of differences in guidance between narcotics recidivists and non-recidivist perpetrators, overcapacity in prisons, a lack of officers, and a low level of supervision. The author's suggestions for overcoming existing obstacles are to separate the guidance given to narcotics recidivists and non-recidivists, improve prison infrastructure, including adding officers, which can improve supervision in prisons.